Machiavelli’s Republic: A Better Place to Be - Christopher Binetti (Britain International for Academic Research (BIAR-Publisher), 2023)
Machiavelli is an underappreciated figure. He is either viewed as an unprincipled, but very Italian figure or treated more fairly, but viewed as a generic European or even Anglicized. This article views Machiavelli as distinctly Italian and as an inheritor of the classical republicanism of Rome on one hand and Aristotle on the other. This article attempts both to explain the modern theory of republicanism and its ancient roots to a wider, more diverse audience and to present Macohiavelli as an Italian thinker, as opposed to as a European thinker. This project is both about ensuring that classical republican is available to persons from all cultures and backgrounds, but also de-Europeanize and de-Anglicize the cultural assumptions around Machiavelli. He is thus best understood as uniquely and irreducibly Italian and also part of a universal movement towards better government. At a time in which majoritarian democracies are out of control all over the world, the checks and balances inherent in classical republicanism serve both as a counterweight and also as a complement to modern democracy.